Guidance and Counseling for Children With Special Needs - Khobirudin Assidiq; Catniya Catniya; Beautiful Azzahra (P3M STAI Kuningan, 2023)
This research departs from the problems that occur in children with special needs. The characteristics of children with special needs differ from one child to another. So that the characteristics and constraints experienced by children with special needs require them to get special education services that should be adapted to the abilities and potential of the child. Children with special needs experience weakness but also have physical, mental, emotional, intellectual or social strengths. The opportunity for ABK to obtain education has expanded along with the introduction of inclusive schools. SLB schools are schools that accept ABK students to study.